Genetic predisposition to pancreatic cancer - Ghiorzo, Paola (Baishideng Publishing Group Inc, 2014)
Pancreatic adenocarcinoma (PC) is the most deadly of the common cancers. Owing to its rapid progression and almost certain fatal outcome, identifying individuals at risk and detecting early lesions are crucial to improve outcome. Genetic risk factors are believed to play a major role. Approximately 10% of PC is estimated to have familial inheritance. Several germline mutations have been found to be involved in hereditary forms of PC, including both familial PC (FPC) and PC as one of the manifestations of a hereditary cancer syndrome or other hereditary conditions. Although most of the susceptibility genes for FPC have yet to be identified, next-generation sequencing studies are likely to provide important insights. The risk of PC in FPC is sufficiently high to recommend screening of high-risk individuals; thus, defining such individuals appropriately is the key. Candidate genes have been described and patients considered for screening programs under research protocols should first be tested for presence of germline mutations in the BRCA2, PALB2 and ATM genes. In specific PC populations, including in Italy, hereditary cancer predisposition genes such as CDKN2A also explain a considerable fraction of FPC.